2003
DOI: 10.1071/ar02102
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil properties and grain yields to deep ripping and gypsum application in a compacted loamy sand soil contrasted with a sandy clay loam soil in Western Australia

Abstract: In the low rainfall, cropping area of Western Australia, massive soil structure due to machinery traffic is common on a range of soil types and is a major obstacle to crop yield improvement. Yield increases on compacted soils have been poor in the last decade compared with those on other soils. An experiment was conducted over 4 years (1997–2000) on a loamy sand soil with massive subsoil structure using a factorial combination of soil ripping to 0.4 m (DR), and application of commercial grade gypsum at 2.5 t/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 20 publications
5
61
0
Order By: Relevance
“…This response increased to 25% in the wetter year of 1999 when the site received 236 mm season rainfall. These results were similar on loamy sand where the response was larger in the wetter year (Hamza and Anderson 2003). This increased response to deep cultivation in wetter years is in accord with other measurements in the region.…”
Section: Discussionsupporting
confidence: 93%
“…This response increased to 25% in the wetter year of 1999 when the site received 236 mm season rainfall. These results were similar on loamy sand where the response was larger in the wetter year (Hamza and Anderson 2003). This increased response to deep cultivation in wetter years is in accord with other measurements in the region.…”
Section: Discussionsupporting
confidence: 93%
“…The Batoka site however, had higher bulk density, soil water content at field capacity and plant available than Chisamba hence soil texture at Batoka was described as loamy sand and Chisamba was Clay loam. The results were in agreement with Hamza and Anderson (2003) who found that Cation exchange capacity and exchangeable calcium increased more on the clayey than on the sandy soil. …”
Section: Soil Characteristics Of the Test Sitessupporting
confidence: 92%
“…Management approaches to ameliorating subsoil compaction, such as deep ripping during cultivation and the application of gypsum to improve soil structure and aggregate stability, have been shown to promote root exploration at depth in the soil profile and to improve grain yield (Hamblin and Tennant 1979;Hamza and Anderson 2003). An added benefit would be to identify genotypic variation among the currentlyavailable Australian wheat cultivars and breeding lines for deep roots that are capable of penetrating a hardpan to access water and nutrients below (Botwright Acuna and Wade 2005).…”
Section: Introductionmentioning
confidence: 98%